Princípios gerais de culturas de células e citometria de fluxo para avaliação dos efeitos da radiação ionizante - Adriana Alexandre dos Santos Tavares (2009)
This report aims to explain in the basic principles of cells culture and flow citometry for the study of ionizing radiation effects on cells culture. Thus, subjects such as cells culture type and advantages/disadvantages of cells culture are explained. Additionally, basic principles of flow citometry, as well as, its applicability for the study of ionizing radiation effects on cell culture are also presented.